Imaging-based parcellations of the human brain. Issue 11 (November 2018) - Eickhoff, Simon; Yeo, B.; Genon, Sarah
Abstract A defining aspect of brain organization is its spatial heterogeneity, which gives rise to multiple topographies at different scales. Brain parcellation — defining distinct partitions in the brain, be they areas or networks that comprise multiple discontinuous but closely interacting regions — is thus fundamental for understanding brain organization and function. The past decade has seen an explosion of in vivo MRI-based approaches to identify and parcellate the brain on the basis of a wealth of different features, ranging from local properties of brain tissue to long-range connectivity patterns, in addition to structural and functional markers. Given the high diversity of these various approaches, assessing the convergence and divergence among these ensuing maps is a challenge. Inter-individual variability adds to this challenge but also provides new opportunities when coupled with cross-species and developmental parcellation studies. The brain can be parcellated into areas or networks with different structural or functional properties. Eickhoff, Yeo and Genon describe various imaging-based strategies to parcellate the human brain, including those based on local properties, such as cytoarchitecture, and global properties, such as connectivity.